IMMIGRATION PROVISIONS AGAINST THE TRAFFIC OF PEOPLE ENTERING / EXITING THE REGION OF INDONESIA - Norbertus Oriwardana; Devina Yuka Utami (Journal of Law and Border Protection, 2020)
This paper is based on CHAPTER III Law no. 6 of 2011 concerning Immigration "Entering and Exiting the Territory of Indonesia". Every foreigner or citizen who wants to enter or leave the territory of Indonesia must go through the Immigration Checkpoint (TPI), if there is a discrepancy and doubt about the validity of the travel document, the immigration officer has the right to refuse to give the person entry or exit stamp. Therefore, immigration has a very vital role in maintaining the country's sovereignty, immigration officers are required to be competent in carrying out their duties. Maintaining state sovereignty through selective policies must be maximized. The need to guard the door of state sovereignty to avoid potential threats that come from various angles.